New morphological data on Cucullanus pinnai pinnai (Nematoda) parasitizing Pimelodus maculatus (Pimelodidae) in southeastern Brazil - Vivian Suane de Freitas Vieira; Fabiano Matos Vieira; José Luis Luque (Revista Brasileira de Parasitologia Veterinária)
This paper describes the morphology of Cucullanus pinnai pinnai parasitizing Pimelodus maculatus in the Guandu River, Brazil, based on differential interference contrast (DIC) microscopy and scanning electron microscopy (SEM), providing new morphological data about this species of parasite. Nematodes were collected between May and October 2012 from specimens of Pimelodus maculatus in the Guandu River (22°48’2”S, 43°37’35”W), in the state of Rio de Janeiro, Brazil. Some characteristics of specimens of Cucullanus in this study fall within the range of morphological variations of previously studied C. pinnai pinnai. Most of the specimens studied here had excretory pore and deirids located at the posterior end of the oesophagus, a feature not recorded in previous studies of this species. In addition, the size of the gubernaculum was larger than the other specimens previously studied. The SEM and DIC analyses of C. pinnai revealed several morphological details of the cephalic region and the tail papillae. With regard to the polymorphism of C. pinnai, morphological and genetic studies of this cucullanid nematode are needed, involving large numbers of host species and a wide geographical distribution.